2016
DOI: 10.1093/cid/ciw157
|View full text |Cite
|
Sign up to set email alerts
|

Safe Reduction in CD4 Cell Count Monitoring in Stable, Virally Suppressed Patients With HIV Infection or HIV/Hepatitis C Virus Coinfection

Abstract: From our data, it can be inferred that CD4 cell count monitoring can be safely performed annually in HIV-monoinfected patients with CD4 cell counts >300 cells/µL and HIV/HCV-coinfected patients with counts >350 cells/µL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…While our results support decreasing CD4 cell count and HIV-RNA monitoring in healthy populations, regular clinic visits remain critical to assess adherence, co-morbidities like HCV coinfection 16 , and psychosocial needs. Finally, our analysis included individuals initiating cART in 2000 or later, yet it is possible that monitoring frequency could have differential effects over calendar time as cART guidelines and prescribing patterns evolve.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…While our results support decreasing CD4 cell count and HIV-RNA monitoring in healthy populations, regular clinic visits remain critical to assess adherence, co-morbidities like HCV coinfection 16 , and psychosocial needs. Finally, our analysis included individuals initiating cART in 2000 or later, yet it is possible that monitoring frequency could have differential effects over calendar time as cART guidelines and prescribing patterns evolve.…”
Section: Discussionmentioning
confidence: 58%
“…Two randomized trials 11,12 and several observational studies, 1316 including ours, 17 focused on CD4 cell and HIV-RNA monitoring strategies in which monitoring frequency is independent of an individual’s time-varying CD4 cell count. While these studies found no clinical harm for annual 1317 or biannual 11,12 monitoring, further follow-up is needed to establish the long-term safety.…”
Section: Introductionmentioning
confidence: 99%
“…PISCIS is an ongoing observational cohort study that has included prospectively all HIV‐infected patients aged ≥ 16 years newly seen in 12 hospitals in Catalonia and two in the Balearic Islands (Spain) since January 1998. The methods applied have been described elsewhere . The PISCIS data set currently contains data for more than 22 000 adults, of whom 13 000 are under active follow‐up.…”
Section: Methodsmentioning
confidence: 99%
“…10,13 Furthermore, there are no treatment strategies to increase CD4 + cell count during periods of viral suppression. A CD4 + count drop below 200 cells/mL is currently seldom observed during successful ART, [14][15][16][17] and frequent testing may cause unnecessary anxiety in patients with clinically inconsequential fluctuations. Therefore, the utility of their monitoring has become a matter of debate.…”
Section: Introductionmentioning
confidence: 99%
“…18 In this context, some guidelines recommend optional or stop monitoring CD4 + cell counts once virological suppressions (VS) are sustained, and the immunological status is stabilized. 1,3,18 There are no randomized comparisons of individuals following different CD4 + count monitoring strategies as they are difficult to be performed, and although it is well established that CD4 + cells falling below 200 cells/mL occur infrequently while viral load is suppressed, [14][15][16][17]19 robust estimates of CD4 + cells dropping below 200 cells/mL over long follow-up are limited. Furthermore, relevant differences might emerge when comparing data collected in countries with different organizations of the social health system.…”
Section: Introductionmentioning
confidence: 99%